INCIDENCE OF PULMONARY THROMBOEMBOLISM IN PATIENTS WITH COVID-19 ADMITTED TO THE INTENSIVE CARE CENTER - Adamczyk, Sheila; César da Silva, Junio; Jaqueline Pereira de Souza, Silvia (Health and Society, 2023)
Introduction: Sars-CoV-2 imposed complex challenges on the global community, on March 11, 2020, when the World Health Organization (WHO) declared COVID-19 as a pandemic, it aroused concern from public and private health institutions internationally, due to to the high proportions of dissemination and risk to global health. Objective: to investigate the incidence of pulmonary thromboembolism (PT) in patients hospitalized for COVID-19 in an Intensive Care Unit (ICU) in southern Brazil. Method: documentary and descriptive research, quantitative approach, through a retrospective analysis of the medical records of patients treated at the ICU. Results: data collection resulted in 306 medical records of patients admitted to the ICU, 64.7% were positive for COVID-19, comprising the sample of interest for the present study, 59% men and 41% women, mean age 53, 8 ± 13.3 years, the constantly cited comorbidities were hypertension, diabetes mellitus and obesity. The sample showed an incidence of PT of 11% in the ICU, the PT+ group had a longer hospital stay compared to the COVID-19 group, angiotomography was performed 7.3 ± 6.3 days after the presence of symptoms compatible with PT, the morbidity and mortality was similar between groups. In the PT+ group, the length of stay and the presence of hypertension were greater than in the COVID-19 group. Conclusion: the understanding that COVID-19 is a respiratory disease, but that through its aggravation, it can evolve into a complication in the coagulative system, predisposing to thrombotic events, is essential, especially to recognize PT early, thus allowing greater chance in the treatment and early diagnosis of this disease.